2021
DOI: 10.3390/cancers13143567
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy in the Treatment of Head and Neck Rhabdomyosarcoma

Abstract: The use of radiation therapy is an important part of multimodality treatment for rhabdomyosarcoma. The specific doses, treatment volumes, and techniques used in radiation therapy can vary dramatically based upon a number of factors including location, tumor size, and molecular characteristics, resulting in complex decisions in treatment planning. This article reviews the principles of evaluation and management for head and neck rhabdomyosarcoma including a summary of the historical studies upon which current m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 71 publications
(108 reference statements)
0
12
0
Order By: Relevance
“…RMS represents a heterogeneous type of sarcomas associated with poor prognosis. Nearly two thirds of patients present RMS before 10 years old with a peak incidence at ages 3 to 5 [27]. RMS could manifest throughout the body with skeletal muscles including head and neck in 40% of patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…RMS represents a heterogeneous type of sarcomas associated with poor prognosis. Nearly two thirds of patients present RMS before 10 years old with a peak incidence at ages 3 to 5 [27]. RMS could manifest throughout the body with skeletal muscles including head and neck in 40% of patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinomas (HNSCCs) are one of the most common malignant cancers ( 1 , 34 , 35 ). The mainstay treatments for HNSCC at the early stage are surgery and/or radiation, which benefit most patients with a good prognosis ( 4 , 36 , 37 ). For HNSCC patients at the advanced or late stages, systematic therapies are recommended, including chemotherapy, targeted therapy, and immunotherapy ( 12 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…For HNSCC patients at the advanced or late stages, systematic therapies are recommended, including chemotherapy, targeted therapy, and immunotherapy ( 12 , 38 , 39 ). Although many HNSCC patients at the advanced/late stages initially respond well to these treatments, most of them will eventually fail and progress to recurrent and/or metastatic diseases ( 2 , 4 , 40 ). For example, a randomized phase III clinical trial to compare the efficacy between different strategies of chemotherapy in advanced HNSCC showed that patients treated by cisplatin and fluorouracil (CF) had a median survival of 8.7 months, as compared to patients administered by cisplatin and paclitaxel (CP) with a median survival of 8.1 months ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of clinical manifestations, the multiplicity of pathological changes, and the different sites of onset make RMS one of the most complex pediatric tumors ( Ramadan et al, 2020 ; Zoroddu et al, 2021 ). Surgical resection, chemotherapy, and radiotherapy are the main treatments for RMS ( van Erp et al, 2018 ; Frankart et al, 2021 ). With the continuous improvement of chemotherapy regimens, the survival rate of RMS patients has increased to 70–80% ( Pappo and Dirksen, 2018 ; Mohammad et al, 2020 ).…”
Section: Roles and Significance Of Circrnas In Pediatric Malignant Solid Tumorsmentioning
confidence: 99%